2006
DOI: 10.1111/j.1365-2109.2005.01423.x
|View full text |Cite
|
Sign up to set email alerts
|

Allozyme variation of hatchery and river populations of rohu (Labeo rohita, Hamilton) in Bangladesh

Abstract: The genetic variations of rohu (Labeo rohita, Hamilton) sampled from five hatchery populations (Arabpur, Brahmaputra, Comilla, Kishorganj and Natore) and three major river populations (the Halda, the Jamuna and the Padma) were analysed by allozyme electrophoresis. Ten enzymes encoded by 11 loci were screened, and six were polymorphic. Alleles at three loci (Est‐1*, Gpi‐1* and Gpi‐2*) proved variable for hatchery and river populations, and the Mdh‐2* locus exhibited heterozygous genotypes for river populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The population genetic structures of L. rohita populations in the Halda, the Jamuna and the Padma rivers, and selected hatcheries (Islam & Alam, 2004;Khan et al, 2006;, Catla catla (Shah & Khan, 2008; have been studied by using RAPD and allozyme markers. Khan et al (2006) using allozyme marker reported 27 % polymorphic loci in the three river population of L. rohita. Das et al (2005) Nei's (1972) developed microsatellite markers obtained all the studied loci polymorphic in an Indian farmed population of L. rohita.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The population genetic structures of L. rohita populations in the Halda, the Jamuna and the Padma rivers, and selected hatcheries (Islam & Alam, 2004;Khan et al, 2006;, Catla catla (Shah & Khan, 2008; have been studied by using RAPD and allozyme markers. Khan et al (2006) using allozyme marker reported 27 % polymorphic loci in the three river population of L. rohita. Das et al (2005) Nei's (1972) developed microsatellite markers obtained all the studied loci polymorphic in an Indian farmed population of L. rohita.…”
Section: Discussionmentioning
confidence: 99%
“…In hybridization study, growth comparison of the reciprocal hybrids is important because they are seldom the same (Tave, Jayaprakash, & Smitherman, 2007). Various genetic studies have been carried out in L. rohita, including DNA fingerprinting by using a sex specific satelite DNA [Bkm 2(8)] and a minisatelite DNA [M13] probes, (Majumdar, Ravinder, & Nasaruddin, 1997), detection of hybrids in the three Indian major carp (catla, rohu and mrigal) using ribosomal DNA RFLP with Xenopus laevis rDNA as a probe (Padhi & Mandal, 1997), RAPD analysis (Barman et al, 2003;Islam & Alam, 2004) and allozyme analysis (Alam, Akanda, Khan, & Alam, 2002;Khan, Rahman, A1am, & Bhuiyan, 2006). Previous studies involving allozyme and RAPD analysis revealed relatively low levels of intra and inter-population genetic variation in the three river populations of rohu and catla (Alam et al, 2002;Islam & Alam, 2004;Islam, Ahmed, Azam, & Alam, 2005) and a wide spread hybridization practices in the hatchery stocks among the three Indian major carp species (Simonsen, Hansen, Mensberg, Serder, & Alam, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Collected fertilized eggs are sold to hatchery owners (Bhuiyan et al, 2019). However, in recent years, the contribution of rohu carp fry (Labeo rohita) to the total production of seeds of Indian major carp has been reduced (Khan et al, 2006). The destruction of fish resources due to indiscriminate capture of brood fish, destruction of spawning ground by cutting the oxbow bend, illegal sands quarrying, and pollution of the river by industrial and agricultural wastes have been a major concern (Alam et al, 2020;Kabir et al, 2015).…”
Section: Production Of Fish Seed From Natural Sourcementioning
confidence: 99%
“…In our country, indigenous species like Labeo rohita have long been cherished for their delicious taste, comprise a significant portion of our culinary traditions since ancient times (Islam et al., 2014 ; Khan et al., 2006 ). The delectable flavour and palatability of fish to high demand in the market, greatly enhancing their commercial value (Khan et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%